2017
DOI: 10.1208/s12249-017-0734-0
|View full text |Cite
|
Sign up to set email alerts
|

Coamorphous Loratadine-Citric Acid System with Enhanced Physical Stability and Bioavailability

Abstract: Coamorphous systems using citric acid as a small molecular excipient were studied for improving physical stability and bioavailability of loratadine, a BCS class II drug with low water solubility and high permeability. Coamorphous loratadine-citric acid systems were prepared by solvent evaporation technique and characterized by differential scanning calorimetry, X-ray powder diffraction, and Fourier transform infrared spectroscopy. Solid-state analysis proofed that coamorphous loratadine-citric acid system (1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 31 publications
1
23
0
2
Order By: Relevance
“…It is known that temperature and moisture affect nucleation and crystal growth. 18) These results suggest that the binary SCL system could enhance stability compared with the SCL of single compound similar to glassy co-amorphous systems. 11,12,19) Therefore KET-ETH (2 : 1) SCL was selected and evaluated as a suitable formulation from the viewpoint of physical stability.…”
Section: Crystal Form Of Scls After Recrystallization Induced By Stimmentioning
confidence: 86%
See 1 more Smart Citation
“…It is known that temperature and moisture affect nucleation and crystal growth. 18) These results suggest that the binary SCL system could enhance stability compared with the SCL of single compound similar to glassy co-amorphous systems. 11,12,19) Therefore KET-ETH (2 : 1) SCL was selected and evaluated as a suitable formulation from the viewpoint of physical stability.…”
Section: Crystal Form Of Scls After Recrystallization Induced By Stimmentioning
confidence: 86%
“…It is known that external stimulus and higher temperature induce nucleation and crystal growth of undercooled compounds. 17,18) Figure 4 shows the XRPD patterns of the recrystallized samples by physical stimulation and storage. Samples except for KET-ETH (1 : 2) before grinding were viscous liquid and confirmed the SCL state.…”
Section: Crystal Form Of Scls After Recrystallization Induced By Stimmentioning
confidence: 99%
“…This is supported by the studies where supersaturation has been most efficiently stabilized when strong intermolecular interactions have been detected between the components, i.e. amorphous salt formation (Ojarinta et al, 2017;Paluch et al, 2010) or hydrogen bonding (Wang et al, 2017). It is also possible that adsorption on the "surfaces" of nuclei and, in some cases solubilization, may inhibit drug recrystallization.…”
Section: Future Prospects: Novel Preparation Methods For Co-amorphousmentioning
confidence: 91%
“…This was also reflected in the pharmacokinetic study in rats, as co-amorphous loratadine-citric acid 1:1 significantly improved absorption and bioavailability of loratadine over that of the crystalline form. Wang et al, 2017 NA=not assessed…”
Section: Na Löbmann Et Al 2011bmentioning
confidence: 99%
“…Similar results reported that formation of salt from sulfamethizole and oxalic acid had a higher melting point than that of each constituent component ( 29 ). The phenomenon of DES-SA was a coamorphous formation that was observed in atorvastatin calcium with nicotinamide ( 30 ), and loratadine with citric acid ( 31 ). Therefore, no peak was observed in the DSC results and PXRD confirming their crystallinity.…”
Section: Discussionmentioning
confidence: 99%